Peranan Metode Ilmiah Dalam Pengembangan Pendidikan Fisika - Ramadani, Gischa Novi; Wahyuni, Nur; Fajari, Alfian; Mahardika, I Ketut; Ernasari, Ernasari; Handono, Sri (Peneliti.net, 2024)
The scientific method is the main foundation in the world of scientific research. The scientific method has been systematically arranged, structured and based on evidence which is used by scientists to conduct scientific research. This article discusses the basic principles of the scientific method, its steps, why you should follow the basic principles and steps of the scientific method, and explains how the scientific method can be integrated into physics education to create a learning environment that focuses on experimentation, observation, and data analysis. This method also encourages students to develop research and creative thinking skills. The aim of the scientific method is to obtain evidence of real and tested results from a problem, so that it can add new discoveries for researchers and new knowledge for the world. Explaining a physics curriculum based on the scientific method can increase students' interest in science and prepare them to face the challenges of our increasingly interconnected and science-based society. This article is based on the results of a previous review of related journals which provides a research basis and in-depth information about the role of the scientific method, then connects it to physics education.